A multicity study of air pollution and cardiorespiratory emergency department visits: Comparing approaches for combining estimates across cities. (November 2018) - Krall, Jenna R.; Chang, Howard H.; Waller, Lance A.; Mulholland, James A.; Winquist, Andrea; Talbott, Evelyn O.; Rager, Judith R.; Tolbert, Paige E.; Sarnat, Stefanie Ebelt
Abstract: Determining how associations between ambient air pollution and health vary by specific outcome is important for developing public health interventions. We estimated associations between twelve ambient air pollutants of both primary (e.g. nitrogen oxides) and secondary (e.g. ozone and sulfate) origin and cardiorespiratory emergency department (ED) visits for 8 specific outcomes in five U.S. cities including Atlanta, GA; Birmingham, AL; Dallas, TX; Pittsburgh, PA; St. Louis, MO. For each city, we fitted overdispersed Poisson time-series models to estimate associations between each pollutant and specific outcome. To estimate multicity and posterior city-specific associations, we developed a Bayesian multicity multi-outcome (MCM) model that pools information across cities using data from all specific outcomes. We fitted single pollutant models as well as models with multipollutant components using a two-stage chemical mixtures approach. Posterior city-specific associations from the MCM models were somewhat attenuated, with smaller standard errors, compared to associations from time-series regression models. We found positive associations of both primary and secondary pollutants with respiratory disease ED visits. There was some indication that primary pollutants, particularly nitrogen oxides, were also associated with cardiovascular disease ED visits. Bayesian models can help to synthesize findings across multiple outcomes and cities by providing posterior city-specific associations building on variation and similarities across the multiple sources of available information. Highlights: Bayesian models can incorporate information across multiple cities and outcomes. Ambient air pollutants are associated with respiratory disease ED visits. Pollutants of primary origin are associated with cardiovascular disease ED visits.